Analysis of cognitive and affective component of environmental literacy of pre-service teachers from Institute of Teacher Education Malaysia - Muda, Azizi; Shaik Ismail, Nazifah; Suandi, Turiman; A. Rashid, Noriati (IDOSI Publications, 2011)
Environmental problems cannot be solved by law alone. One of the effective ways to overcome environmental crisis is by developing environmentally literate society. Education is claimed to be the most promising measures in developing any society. Thus, teachers themselves have to be environmentally literate and competent enough in producing informed learners who can make environmentally responsible decisions and portrays environmental responsible behavior. In coherent with the need to produce environmentally literate teachers, Environmental Education course was introduced in the Institutes of Teacher Education in 2001 and was fully implemented by 2003. This aim of this paper is to present the preliminary analysis of cognitive and affective component of environmental literacy of pre-service teachers who have undergone the environmental education course. This preliminary research utilizes quantitative research design. The descriptive survey method was used to gather required information from the respondents. The respondents were 254 pre-service teachers enrolled under post-graduate program from 12 Institute of Teacher Education of Malaysia. The findings were tabulated using descriptive statistics.